Ethics and politics in Locke: from human rights to humans without rights - Polo Santillán, Miguel Ángel (2021)
The paper presents the main lines of political and ethical thought of John Locke, one of the most influential philosophers on modern thought. Since it is felt the double standards with which Locke build your political theory, claiming universal rights to justify slavery then, just war, domination, accumulation of wealth on the part of bourgeois society. Made that mark the modern political thought and practice.